Prevalence of Genu Valgum in Children Aged 10-12 Years with Excessive Body Weight (Overweight/Obesity) in Sanur Kaja Village, Denpasar - Vidya Rahmayunissa Swandi Putri; Ni Wayan Tianing; Agung Wiwiek Indrayani; Ari Wibawa; Sayu Aryantari Putri Thanaya (Jurnal Epidemiologi Kesehatan Komunitas, 2020)
Background: Overweight/obesity is a global health problem, both in developed and developing countries and the number of overweight/obese people increases every year. Being overweight during childhood increases the risk of obesity in adulthood and can lead to musculoskeletal disorders, one of which is genu valgum. The purpose of this study was to determine the prevalence of genu valgum in children aged 10-12 years who are overweight/obese in Sanur Kaja Village, Denpasar.Methods: This study was an observational study with a cross-sectional design conducted at elementary schools in Sanur Kaja Village in April 2019. The sampling technique used was purposive sampling. A total of 78 children were included in this study. The univariate analysis in this study was genu valgum, overweight/obesity, age, and gender.Result: The prevalence of genu valgum in children aged 10-12 years in Sanur Kaja Village was 46.7% in overweight children and 53.3% in obese children, with 30 people (38.5%) experiencing genu valgum out of the total sample of 78 people (100%).Conclusion: Based on the result of this study, the incidence of genu valgum was higher in children aged 10-12 years who were obese compared to children with overweight body mass index.  It is recommended that children who are obese and overweight to control their eating patterns, maintain normal body weight, and do enough physical activity.